2023
DOI: 10.1002/mc.23602
|View full text |Cite
|
Sign up to set email alerts
|

m6A reader YTHDF3 triggers the progression of hepatocellular carcinoma through the YTHDF3/m6A‐EGFR/STAT3 axis and EMT

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the fourth leading cause of tumor‐related deaths worldwide. N6‐methyladenosine (m6A) mediates RNA metabolism in tumor biology. However, the regulatory role of YTHDF3, an m6A reader, in HCC progression and its underlying mechanisms remains unclear. Therefore, this study aims to investigate the oncogenic effect of YTHDF3 on HCC progression via the epigenetic regulation of m6A‐modified mRNAs. The expression levels of YTHDF3 in HCC tissues and matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Su et al (2021) found that YTHDF1 promoted HCC cell viability and metastasis by facilitating the translation of EGFR. YTHDF3 also plays a role in promoting EGFR translation (Hu et al, 2023). However, an alternative study yielded contrasting results, indicating that m 6 A methylation and subsequent posttranscriptional destabilization of EGFR by METTL14 inhibit HCC cell migration, invasion, and EMT process (Shi et al, 2020).…”
Section: The Involvement Of M 6 a Function In Hcc Tumorigenesismentioning
confidence: 99%
“…Su et al (2021) found that YTHDF1 promoted HCC cell viability and metastasis by facilitating the translation of EGFR. YTHDF3 also plays a role in promoting EGFR translation (Hu et al, 2023). However, an alternative study yielded contrasting results, indicating that m 6 A methylation and subsequent posttranscriptional destabilization of EGFR by METTL14 inhibit HCC cell migration, invasion, and EMT process (Shi et al, 2020).…”
Section: The Involvement Of M 6 a Function In Hcc Tumorigenesismentioning
confidence: 99%